The presence of a FLT3 internal tandem duplication in patients with acute myeloid leukemia (AML) adds important prognostic information to cytogenetic risk group and response to the first cycle of chemotherapy: analysis of 854 patients from the United Kingdom Medical Research Council AML 10 and 12 trials. - Kottaridis, P; Gale, R; Frew, M; Harrison, G; Langabeer, SE; Belton, A; Walker, H; Wheatley, K; Bowen, D; Burnett, A; Goldstone, A; Linch, D (2001)
In acute myeloid leukemia (AML), further prognostic determinants are required in addition to cytogenetics to predict patients at increased risk of relapse. Recent studies have indicated that an internal tandem duplication (ITD) in the FLT3 gene may adversely affect clinical outcome. This study evaluated the impact of a FLT3/ITD mutation on outcome in 854 patients, mostly 60 years of age or younger, treated in the United Kingdom Medical Research Council (MRC) AML trials. An FLT3/ITD mutation was present in 27% of the patients and was associated with leukocytosis and a high percentage of bone marrow blast cells (P <.001 for both). It had a borderline association with a lower complete remission rate (P =.05) and a higher induction death rate (P =.04), and was associated with increased relapse risk (RR), adverse disease-free survival (DFS), event-free survival (EFS), and overall survival (OS) (P <.001 for all). In multivariate analysis, presence of a mutation was the most significant prognostic factor predicting RR and DFS (P <.0001) and was still significant for OS (P =.009) and EFS (P =.002). There was no evidence that the relative effect of a FLT3/ITD differed between the cytogenetic risk groups. More than one mutation was detected in 23% of FLT3/ITD(+) patients and was associated with worse OS (P =.04) and EFS (P =.07). Biallelic disease or partial/complete loss of wild-type alleles was present in 10% of FLT3/ITD(+) patients. The suggestion is made that detection of a FLT3/ITD should be included as a routine test at diagnosis and evaluated for therapeutic management.